1999
DOI: 10.1073/pnas.96.5.1915
|View full text |Cite
|
Sign up to set email alerts
|

Native display of complete foreign protein domains on the surface of hepatitis B virus capsids

Abstract: The nucleocapsid of hepatitis B virus (HBV), or HBcAg, is a highly symmetric structure formed by multiple dimers of a single core protein that contains potent T helper epitopes in its 183-aa sequence. Both factors make HBcAg an unusually strong immunogen and an attractive candidate as a carrier for foreign epitopes. The immunodominant c͞e1 epitope on the capsid has been suggested as a superior location to convey high immunogenicity to a heterologous sequence. Because of its central position, however, any c͞e1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
189
2
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 235 publications
(196 citation statements)
references
References 50 publications
3
189
2
2
Order By: Relevance
“…However, since the particle-forming ability of such fusion proteins frequently decreased with increasing insert size, the c/e1 loop was thought to have a limited insertion capacity. This assumption was disproved with our finding that CLP are able to display the entire 238-aa green fluorescent protein (GFP) in its native form on their surface [34].…”
Section: Introductionmentioning
confidence: 58%
“…However, since the particle-forming ability of such fusion proteins frequently decreased with increasing insert size, the c/e1 loop was thought to have a limited insertion capacity. This assumption was disproved with our finding that CLP are able to display the entire 238-aa green fluorescent protein (GFP) in its native form on their surface [34].…”
Section: Introductionmentioning
confidence: 58%
“…The cloning and construction of the cDNA encoding the mouse cardiac muscle RyR2 wt have been described previously (20). The cDNA of RyR2 D4365-GFP was designed such that the entire GFP sequence, with Gly-rich spacers on each side (19), is inserted after the Asp-4365 in the DR1.…”
Section: Construction Expression and Purification Of Ryr2 Wt Andmentioning
confidence: 99%
“…To further minimize potential disruptive effects of the insertion on folding of both GFP and RyR2, two Gly-rich spacers were added to flank either side of the GFP (19).…”
Section: Three-dimensional Reconstruction Of Recombinant Ryr2mentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier it was shown that failure of some chimeric proteins to assemble into VLPs could be explained by the length of the insert; 120 amino acids are usually accepted as a maximum. On the other hand, Kratz et al 36 reported successful insertion of the GFP protein (238 amino acids) in the HBc; thus the structural importance of proper and independent folding of foreign sequences was clearly demonstrated. The potential role of different characteristics in the efficient assembly of VLPs was addressed in numerous studies, such as β-sheet forming properties, the distance between the N and the C-terminus, and volume and hydrophobicity of the amino acids of the insert.…”
Section: Discussionmentioning
confidence: 99%